PENGARUH LEARNING QUALITY PENDIDIKAN PANCASILA TERHADAP HASIL TES FORMATIF PESERTA DIDIK SMP NEGERI 29 BANDAR LAMPUNG - Yosia Manurung; Yunisca Nurmalisa; Rohman; Berchah Pitoewas; Elisa Seftriyana (STKIP Subang, 2026)
This study is motivated by the importance of learning quality in improving students’ cognitive achievement, particularly in Pancasila Education. Preliminary observations at SMP Negeri 29 Bandar Lampung indicated that students’ formative test results were not optimal and not evenly distributed. This study aims to determine the effect of learning quality on students’ formative test results. The research employed a quantitative approach with an associative design. The population consisted of 233 students, with a sample of 70 respondents selected through simple random sampling. Data were collected using questionnaires and tests and analyzed using simple linear regression with the assistance of SPSS version 27. The results showed that learning quality has a significant effect on students’ formative test results, as indicated by a significance value of less than 0.05. This finding implies that better learning quality leads to higher student achievement in formative assessments.